Experimental Investigation of Square Pin Fins Geometry Variations with Aligned and Staggered Arrangements Under Forced Convection Heat Transfer - Nimesh Limbasiya; Sagar Mane Deshmukh (Frontier Advances in Applied Science and Engineering, 2025)
This research was conducted to determine the heat transfer characteristics of pin fins with variations in square, diamond, and combination (diamond-square) geometries. The heat transfer that occurs in the pin fins is a type of forced convection heat transfer. The research experiment used a TD1005 free and forced convection equipment with inline and staggered pin fin arrangement. The dimensions of the pin fin used are a height of 73 mm and a side of 10 mm, and a base plate measuring 101 mm x 101 mm. The material used is type 6061 aluminum. The maximum convection coefficient values for all power variations are in variations of square geometry and staggered arrangement, as well as for the Nusselt number, which has the same correlation with the convection coefficient results. The performance of the use of fins indicated on the effectiveness value for all variations suggests that it is suitable for use on the device, however, the efficiency of the pins demonstrates that the combination (diamond-square) for aligned and staggered arrangement produces the best results.